2016
DOI: 10.3109/08880018.2016.1173148
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and mortality prognostic factors in childhood adrenocortical tumors: Analysis from the Brazilian National Institute of Cancer experience

Abstract: Prognostic markers that can help identifying precocious risk of unfavorable outcomes in patients with childhood adrenocortical tumors (ACTs) are still unclear. This observational and retrospective study aimed to identify clinical and pathology prognostic factors of recurrence and death in a tertiary cancer center population. Clinical, pathology, demographic, staging, and therapy data from patients with childhood ACT (median age: 3.6 years) treated at the Brazilian National Institute of Cancer between 1997 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…observed that large size and heterogeneous structure often coincide with the malignant nature of the tumors. Although tumor size is assessed with different units of measures by different authors (volume, diameter, or weight), the concept that huge ACCs have a worse prognosis is shared by most (Supplementary Table S1) …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…observed that large size and heterogeneous structure often coincide with the malignant nature of the tumors. Although tumor size is assessed with different units of measures by different authors (volume, diameter, or weight), the concept that huge ACCs have a worse prognosis is shared by most (Supplementary Table S1) …”
Section: Discussionmentioning
confidence: 74%
“…13 The Interna- Supplementary Table S1). 1,14,19,20,27,29,30 At diagnosis, most ACCs occurring in children are localized and can be completely resected. 14,20 An initial surgical excision in our series was attempted in most cases (66/82), but the complete resection was possible only in 37.8% of the whole population (31/82) and in 45.2% of the patients with localized disease (28/62), confirming the difficulty in excising these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, to date, only eight case reports and one small case series of six patients in the literature have reported on patients with ACC who have achieved long‐term survival of more than 10 years . Of note, various clinical and pathologic factors such as tumor size , lymphadenectomy , major venous involvement , margin status , and higher Weiss score have not been consistently associated with long‐term survival following resection of ACC. Therefore, the objective of the current study was to use a multi‐institutional collaborative database of ACC patients in the United States to identify characteristics of actual 5‐ and 10‐year survivors following resection of ACC.…”
Section: Introductionmentioning
confidence: 99%